PHYTOCHROME-INTERACTING FACTOR-LIKE14 and SLENDER RICE1 Interaction Controls Seedling Growth under Salt Stress. Issue 1 (24th June 2020) - Mo, Weiping; Tang, Weijiang; Du, Yanxin; Jing, Yanjun; Bu, Qingyun; Lin, Rongcheng
Abstract: A transcriptional module integrates the light and gibberellic acid signaling pathways to precisely control rice seedling growth under salt stress. Abstract: Early seedling development and emergence from the soil, which are critical for plant growth and important for crop production, are controlled by internal factors, such as phytohormones, and external factors, such as light and salt. However, little is known about how light and salt signals are integrated with endogenous cues in controlling plant physiological processes. Here, we show that overexpression of rice ( Oryza sativa ) PHYTOCHROME-INTERACTING FACTOR-LIKE14 (OsPIL14) or loss of function of the DELLA protein SLENDER RICE1 (SLR1) promotes mesocotyl and root growth, specifically in the dark and under salt stress. Furthermore, salt induces OsPIL14 turnover but enhances SLR1 accumulation. OsPIL14 directly binds to the promoter of cell elongation-related genes and regulates their expression. SLR1 physically interacts with OsPIL14 and negatively regulates its function. Our study reveals a mechanism by which the OsPIL14-SLR1 transcriptional module integrates light and gibberellin signals to fine-tune seedling growth under salt stress, enhancing understanding about how crops adapt to saline environments.